Los recursos naturales y el medio ambiente en la economía de mercado - Londoño, Claudia Lilián (Universidad de San Buenaventura - Cali, 2017)
This article presents an analysis of the current economic system and its relation with the global environment, through a general introduction to the topic of natural resources. It reviews the initial tools with which Economics, as a discipline, approaches the study of environmental goods and services, and outlines the transition from neoclassic to ecological economics.